Análisis jurídico y social para la creación del centro carcelario en el cantón La Maná - Ortega Granja, Galo Rodrigo (2012)
This research aims to determine whether the lack of Jail Center in Canton La Mana, affects the poor reintegration of the offender into society, in order to suggest the creation of the jail facility in the town and improve the process of improving people who have been released who have rights, non-discrimination, work, respect for their dignity as a person, to the effect we used descriptive research field mode, the survey of legal practitioners in free exercise lamanense community, the judicial authorities, the results were that the defendants are not prepared to return to society, because they have not received sufficient education in Jail Center also that society discriminates against people who have been in prison because they are deemed more dangerous than a criminal who has not gone through the prison.